How well do policymakers address stigma surrounding substance use disorders: lessons from a qualitative review of Scottish Alcohol and Drug Partnerships’ strategic plans - Falconer, Robin; Tang, Jason (Frontiers in Public Health, 2023)
Background Stigma is a significant barrier to the successful implementation of public health policies which aim to reduce harm from substance use disorders. Despite attention being given to stigma in the literature for at least a decade, evidence on what works to reduce it is limited and inconclusive. Without clear guidance, policymakers could be limited in their ability to develop evidence-informed strategies for reducing stigma. In response to a steep incline in drug-related deaths in Scotland since 1996, the Scottish Government has committed to tackling stigma in national drug policy. Scotland’s 31 Alcohol and Drug Partnerships are responsible for developing local strategies that aim to tackle harm from substance use disorders. This qualitative review explored how well these strategies respond to stigma and identified approaches mentioned that could have implicit implications for tackling stigma. Methods The strategic plans of Alcohol and Drug Partnerships across Scotland were identified and thematically analysed to identify key themes relating to stigma. Content of strategic plans was initially coded under a coding scheme of four broad categories: content that explicitly mentioned stigma; identity, status and power; deservedness of support; and attribution of responsibility for SUDs. Results Twenty-four strategic plans were identified and analysed, with four themes emerging: (1) limited clarity and consistency on how stigma will be directly tackled by ADPs; (2) recognition of the positive contribution that people with substance use disorders can make towards decisions about treatment and support; (3) diversion of people with substance use disorders away from the criminal justice system towards quality support underpinned by human rights; and (4) recognition of the complex determinants of substance use disorders and that everyone has a role to play. Conclusion Alcohol and Drug Partnerships acknowledged the importance of tackling stigma in their strategic plans but provide limited clarity on how this will be done. This review calls for the inclusion of more evidence-informed strategies for tackling stigma within the Scottish local policymaking context. This requires academic, policymaking and lived experience communities to collaborate to test and evaluate innovative responses to tackling in stigma to strengthen understanding of what works in which contexts.